Pathology Of Formulation And Implementation Of Monetary Resources Policies And Its Allocation In The Country's Banking System - Mohamad mahdi Sharifnia; Naser Mirsepasi; Abolhasan Faghihi (پژوهش‌های مدیریت عمومی, 2023)
AbstractThe lack of a coherent decision-making and policy-making system has caused several consequences and damages in the society, which need to be identified. These consequences extend from the lack of order in the work flow of society and related economic systems, to the distortion of the economic division of labor system and the creation of extensive outstanding claims in the banking system; On the other hand, the future of economic organizations such as banks depends on government policies, especially that banks are completely aligned with government policies and policies. The current research is based on the practical goal and has been carried out in 3 phases and a multi-stage process. The first phase is the recognition and explanation of the research plan, which includes the preparation of the research plan, the preliminary study related to the theoretical foundations of research in the field of pathology, the formulation and implementation of policies, and the explanation of the main concepts. In the second phase, according to the findings of the first phase, interviews were compiled. In-depth interviews were conducted with managers, experts and planners of Iran's banking system and professors of public administration (policy trends, organizational behavior, human resources). Then, using the qualitative approach (Delphi method), the modeling of various aspects of pathology was discussed, formulation and implementation of policies in the field of monetary resources and its allocation. In the stage of identifying the issues, the use of academic experts and experts in the field of the subject area of ​​the research, as well as experts in the National Bank of Iran, have been the intended community. Sampling at this stage is a targeted type of reference, which is a non-probability method. In this research, selected samples include 10 senior managers of Iran's banking system and 5 academic experts. The issues, problems and harms of policy making in the banking system in the field of resources and expenditure management, including policy enforcers, the structure of laws and policy implementing organizations, resources and facilities, organizational policies, legal policies, systemic corruption, pressure groups, related stakeholders, Economic indicators and internal processes are damages. The result is that the structure of the banking system needs fundamental changes, so the new structure must be redesigned in accordance with the goals defined in the law for the organization and appropriate human and organizational resources must be attracted so that laws and policies can be implemented well in a suitable and new context.IntrodutionThe lack of a coherent system of decision-making and policy-making has caused several consequences in society. These consequences range from the lack of order in the workflow of society and related social systems, to the distortion of the system of division of social and economical  labor.Case study:Country's Banking SystemMaterials and Methods The present study is based on an applied goal and has been carried out during 3 phases and a multi-stage process. The first phase of recognizing and explaining the research plan; Phase 2 According to the findings of the first phase, interviews were initially developed. Then, using a qualitative approach (Delphi method), various aspects of pathology were modeled and policies were developed and implemented in the field of monetary resources and its allocation. Experts and academic experts in the field of subject matter research as well as experts in the National Bank of Iran have been the target community. Sampling At this stage, 15 people were selected from the target reference type.Discussion and Results Issues including: including policy enforcers, policy structure and policy implementing organizations, resources and facilities, organizational policies, legal policies, systemic corruption, pressure groups, dependent stakeholders, economic indicators, internal processes of policy violations ‌ are transitions.Conclusion The structure of the banking system needs fundamental changes and therefore the new structure should be in accordance with the objectives defined in the law for the redesign organization and the appropriate manpower and organizational to be absorbed in a new appropriate context, laws and policies are well implemented.